Pengaruh Zakat Infaq Shadaqah Terhadap Penurunan Kemiskinan di Indonesia Tahun 2010-2020 - Risda Ridwanayati; Ade Yunita Mafruhat (UNISBA Press, 2023)
Abstract Poverty is a condition of inability both individually, in families and in groups to meet the basic needs of life (clothing, food and shelter). This study entitled